Care and feeding of sprites - DiTerlizzi, Tony.; Black, Holly (New York : Simon & Schuster Books for Young Readers, 2006)
A guide from the International Sprite League on how to recognize true sprites, how to catch them, and how to care for them and keep them happy.
Fakulti Teknologi Kreatif dan Warisan
Keywords: Fairies -- Fiction